APLIKASI PENGELOLAAN INVENTARIS BARANG DI SMK NEGERI 1 PLAMPANG BERBASIS WEB - Yudi Mulyanto; Fery Ramdani (Jurnal Informatika Teknologi dan Sains, 2019)
Inventory of goods is an activity of recording goods as well as processing data on inventory of goods owned by a school. In educational institutions, school facilities and infrastructure are very important. Facilities and infrastructure are useful to support the implementation of the teaching and learning process, both directly and indirectly in an institution, to achieve educational goals. Good data management will provide great benefits for smoothness and success in the activities of an organization. Research with the title "Application Inventory Management Application at Vocational School 1 Plampang". Problem formulation: How to design and build an Inventory Management Application in SMK Negeri 1 Plampang ?. Objective: To design and build an Inventory Management Application in SMK Negeri 1 Plampang. Research Methods: Descriptive with a qualitative approach. The data collection methods used are observation, interviews, and literature. The software development method used in designing the Inventory Management Application at SMK Negeri 1 Plampang is a waterfall. The data sources used are primary data and secondary data. Conclusion: This application can help employees of administration at SMK Negeri 1 Plampang in managing goods data such as fading in the search for data and when making reports.